2021
DOI: 10.1155/2021/5573937
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer T (NKT) Cells and Periodontitis: Potential Regulatory Role of NKT10 Cells

Abstract: Natural killer T (NKT) cells constitute a unique subset of T lymphocytes characterized by specifically interacting with antigenic glycolipids conjugated to the CD1d receptor on antigen-presenting cells. Functionally, NKT cells are capable of performing either effector or suppressor immune responses, depending on their production of proinflammatory or anti-inflammatory cytokines, respectively. Effector NKT cells are subdivided into three subsets, termed NKT1, NKT2, and NKT17, based on the cytokines they produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 112 publications
1
4
0
Order By: Relevance
“…Similar to our findings, previous research revealed a greater number of NKT recruited in periodontitis tissues (Muthukuru, 2012 ;Yamazaki et al, 2001 ). Several studies have demonstrated the tissuespecific function of NKT and highlighted its pathogenic role in periodontitis (Aoki-Nonaka et al, 2014 ;Melgar-Rodríguez et al, 2021 ), which may be attributed to the proinflammatory and immunoregulatory activities mediated by NKT, spanning from cytokine production to immune cell interactions (Seidel et al, 2020 ).…”
Section: Several Lymphocyte Subsets Casually Associated With the Risk...supporting
confidence: 90%
“…Similar to our findings, previous research revealed a greater number of NKT recruited in periodontitis tissues (Muthukuru, 2012 ;Yamazaki et al, 2001 ). Several studies have demonstrated the tissuespecific function of NKT and highlighted its pathogenic role in periodontitis (Aoki-Nonaka et al, 2014 ;Melgar-Rodríguez et al, 2021 ), which may be attributed to the proinflammatory and immunoregulatory activities mediated by NKT, spanning from cytokine production to immune cell interactions (Seidel et al, 2020 ).…”
Section: Several Lymphocyte Subsets Casually Associated With the Risk...supporting
confidence: 90%
“…Similar to our findings, previous research revealed more NKT recruited in periodontitis tissues ( Muthukuru, 2012 ; Yamazaki et al, 2001 ). Several studies have demonstrated the tissue-specific function of NKT and highlighted its pathogenic role in periodontitis ( Aoki-Nonaka et al, 2014 ; Melgar-Rodríguez et al, 2021 ), which may be attributed to the proinflammatory and immunoregulatory activities mediated by NKT, spanning from cytokine production to immune cell interactions ( Seidel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, previous research revealed a greater number of NKT recruited in periodontitis tissues ( Muthukuru, 2012 ; Yamazaki et al, 2001 ). Several studies have demonstrated the tissue-specific function of NKT and highlighted its pathogenic role in periodontitis ( Aoki-Nonaka et al, 2014 ; Melgar-Rodríguez et al, 2021 ), which may be attributed to the proinflammatory and immunoregulatory activities mediated by NKT, spanning from cytokine production to immune cell interactions ( Seidel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%